Role model video encouraging rural women participating in community planning - Kosec, Katrina; Kyle, Jordan; Nayarayan, Sudha; Raghunathan, Kalyani (CGIAR System Organization, 2024)
Empowering Women: A Video to promote Inclusion in India’s Government Planning.